2020
DOI: 10.21873/anticanres.14512
|View full text |Cite
|
Sign up to set email alerts
|

YM155 Reverses Cabazitaxel Resistance in Castration-resistant Prostate Cancer by Reducing Survivin Expression

Abstract: Background/Aim: The purpose of the present study was to clarify whether treatment with YM155, a novel small-molecule inhibitor of survivin, reversed cabazitaxel resistance in castration-resistant prostate cancer (CRPC). Materials and Methods: Cabazitaxel resistance was induced in the castration-resistant prostate cancer cell line, 22Rv1-CR. In vitro and in vivo models were used to test the efficacy of YM155 and cabazitaxel. Results: Survivin gene expression was significantly higher in 22Rv1-CR than its parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The first confirmed survivin inhibitor, YM155, can target the survivin promoter, inhibit the transactivation of survivin, and reduce the expression of survivin protein. 25 , 26 We have confirmed that the proliferation activity and survivin expression of cells were most significant for 10 ng/mL TGF-β1 ( Fig. 3 A).…”
Section: Resultssupporting
confidence: 64%
“…The first confirmed survivin inhibitor, YM155, can target the survivin promoter, inhibit the transactivation of survivin, and reduce the expression of survivin protein. 25 , 26 We have confirmed that the proliferation activity and survivin expression of cells were most significant for 10 ng/mL TGF-β1 ( Fig. 3 A).…”
Section: Resultssupporting
confidence: 64%
“…As a sort of next-generation cancer biomarker, survivin mRNA can offer potential diagnostic information for cancer care, and thus, exploring an efficient analytical approach to accomplish a monitoring task at the cellular level is of great necessity. 27 To this aim, two groups of HeLa cells are treated in turn with different concentrations of the survivin inhibitor [sepantronium bromide (YM155)] 33 to realize a target downregulation phenomenon. In comparison to the untreated cells (top images in Figure S18A), the incremental additions of YM155 give rise to a dramatically decreased Cy5 fluorescence (middle and bottom images in Figure S18A), and such a finding can be explained by the fact that the reduced survivin mRNA lessens the walking frequency.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…4 Cabazitaxelresistant 22Rv1-CR cells were also generated previously. 5 Cell culturing was basically performed as previously reported. 14 PC-3-TxR/CxR and DU145-TxR/CxR cells were cultured in RPMI-1640 medium (Fujifilm Wako, Osaka, Japan) with 3 nM cabazitaxel (Fujifilm Wako) to maintain their drug resistance.…”
Section: Cell Cultures and Transfectionmentioning
confidence: 99%
“…3 We previously cultured PC cells in medium containing cabazitaxel for an extended time and established a cabazitaxel-resistant cell line as a tool to search for effective drugs. 4,5 L-type amino acid transporter 1 (LAT1, SLC7A5) is an amino acid transporter expressed on the plasma membrane of various types of cancer cells. 6 Our group has demonstrated that LAT1 plays a pivotal role in cancer cell proliferation through the activation of the mammalian target of rapamycin (mTOR) pathway in urologic cancers, including PC.…”
Section: Introductionmentioning
confidence: 99%